Design of water debinding and dissolution stages of metal injection moulded porous Ti foam production. (15th December 2015) - Shbeh, Mohammed Menhal; Goodall, Russell
Abstract: Foams are advanced materials with controlled meso- and micro-structure, with huge potential in a variety of applications such as in the biomedical and automotive sectors. One promising technique for the production of Ti foams is Metal Injection Moulding in combination with Space Holders (MIMSH). Most existing work in the literature on MIM-SH foams reports very long debinding and dissolution periods that can extend for more than two days. In this paper, the effect on process speed of different water debinding and dissolution techniques of MIM-SH Ti foams will be investigated. Furthermore, the temperature influence on the debinding and dissolution behaviour of a PEG based binder and KCl space holder will be examined. In addition, some debound samples will be sintered in order to verify their suitability for the production of Ti foams. The results show that a heated ultrasonic bath is the fastest and most effective technique in removing the PEG and space holder, while increasing the temperature increased the removal rate up to a certain temperature (80 °C) where a significant swelling occurred, leading to a slower removal rate. The results make it possible for a more rapid production method to be designed systematically. Graphical abstract: Highlights: Early stage debinding rate of MIM Ti foams is surface area dependent. Rate increases with temperature up to 80 °C; beyond this it is reduced by swelling. Ultrasonic treatment further decreases debinding and dissolution time. A chart to permit selection balancing process temperature and time is provided.